Effects of Industrial and Ruminant Trans-fatty Acids-Enriched Diet on Fecal Microbiome and Short Chain Fatty Acid Metabolites of C57BL/6 Mice. (7th June 2021) - Mohammadi, Farzad; Tolsdorf, Emma; Greffard, Karine; Chotard, Élodie; Bilodeau, Jean-François; Foster, Jane; Bertrand, Nicolas; Rudkowska, Iwona
Abstract: Objectives: We hypothesized that the intake of industrially originated trans-fatty acids (elaidic acid (EA trans 18: 1n-9)) and ruminant trans fatty acids (trans-palmitoleic acid (TPA t16:1 n-7)) will differentially modify gut microbiota and short-chain fatty acids (SCFA) profiles. The objective is to compare the long- and short-term effects of EA and TPA on the fecal microbiome and SCFAs profiles in mice. Methods: Forty C57BL/6 mice were divided to 4 groups. Each group was given one of the following 4 formulations in the drinking water: lecithin nanovesicles, nanovesicles containing either lecithin with EA or TPA (86:14 (w/w)) or water alone (control) for 28 days with a normal fat diet. Fecal samples were collected at days 0, 7 and 28. Gut microbiota profiles were determined by 16S rRNA gene sequencing. SCFAs were measured by headspace gas chromatography coupled to a single quadrupole mass spectrometer. Baseline data (relative abundance of bacteria or levels of SCFAs) was pooled and then compared with data from day 7 or day 28 for each formulation. Results: After 7 days of lecithin, 16S rRNA analysis revealed an increase in the relative abundance of Lactobacillus. After 28 days of lecithin, an increase in the relative abundance of Lactobacillus, Erysipelotrichaceae, and Enterobacteriaceae together with a decrease in Bacteroidaceae was observed. Further, a tendency to increase level of butyric acid ( P = 0.053) was observed after 28 days of lecithin. After 7 days of EA, an increase in the relative abundance of Lactobacillus, whereas a decrease in the relative abundance of Parabacteroides, Bacteroides, Rumininococcaceae, Lachnospiraceae and Peptococcaceae was observed. After 7 days of TPA, results show a decreased level of isovaleric acid ( P = 0.04) and valeric acid ( P = 0.03). After 28 days of TPA, data demonstrates an increase in the level of butyric acid ( P = 0.01) and propionic acid ( P = 0.01). Water intake for 28 days decreased the level of valeric acid ( P = 0.02). Conclusions: Consumption of industrial and ruminant trans-fatty acids modify differentially bacterial taxa present in the gut microbiome and SCFA profiles. Funding Sources: NSERC, CMDO.